Condemned As A Nihilist; A Story of Siberia - G. A. George Alfred Henty
There are few difficulties that cannot be surmounted by patience, resolution, and pluck, and great as are the obstacles that nature and the Russian government oppose to an escape from the prisons of Siberia, such evasions have occasionally been successfully carried out, and that under far less advantageous circumstances than those under which the hero of this story undertook the venture. For the account of life in the convict establishments in Siberia I am indebted to the very valuable books by my friend the Rev. Dr. Lansdell, who has made himself thoroughly acquainted with Siberia, traversing the country from end to end and visiting all the principal prisons. He conversed not only with officials, but with many of the prisoners and convicts, and with Russian and foreign residents in the country, and his testimony as to the management of the prisons and the condition of the convicts is confirmed by other independent writers personally cognizant of the facts, and like him able to converse fluently in the language, and writing from intimate knowledge of the subject. G. A. HENTY. (Typographical errors above are due to OCR software and don't occur in the book.)